Standard Theories of Emotion and the Concept of Intentionality - Thomas Eneji Ogar (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2022)
In traditional Western philosophy, it was widely accepted that emotions could be an obstacle to human rationality when it comes to attempting to gain objective knowledge and truth. One way of understanding emotions is that they may accidentally happen to us; they are a purely non-volitional form of a mental phenomenon. There is the question of whether the study of emotions needs to rely on scientific methods at all. Can emotions be investigated merely through conceptual analysis and introspection? Are emotions only accessed, felt, and even understood from the first-person perspective? If the answer is positive, it indicates that we should have to refute pieces of subpersonal empirical evidence regarding the neurophysiological activities of emotions. This paper concerns the philosophical debate on emotion. I argue that in the history of the philosophy of emotion, the competing theories place themselves either on "cognitive" or "bodily" grounds; both are responsible for the mind-body dichotomy and have their difficulties. The former is what I call the "Orthodox Feeling Theory," which cannot account for the structure of intentionality or the evaluative property of emotions; the latter is the "Strong Cognitive Theory," which ignores the role of the bodily and experiential aspects. Such standard theories are out of date.